DESEMPEHO ZOOTÉCNICO DE CURIMBAS EM SISTEMA BIOFLOCOS - LIMA, Jéssica Julian Fernandes; OLIVEIRA, Fúlvia Cristina; SANTO, Fayane Espirito; CALVES, Gleice de Souza; ACUNHA, Rubia Mara Gomes; CAMPOS, Cristiane Meldau (ANAIS DO ENIC, 2018)
-